Continuous-flow enantioselective α-aminoxylation of aldehydes catalyzed by a polystyrene-immobilized hydroxyproline - Cambeiro, Xacobe C.; Martín-Rapún, Rafael; Miranda, Pedro O.; Sayalero, Sonia; Alza, Esther; Llanes, Patricia; Pericàs, Miquel A. (Beilstein Journal of Organic Chemistry, 2011)
The application of polystyrene-immobilized proline-based catalysts in packed-bed reactors for the continuous-flow, direct, enantioselective α-aminoxylation of aldehydes is described. The system allows the easy preparation of a series of β-aminoxy alcohols (after a reductive workup) with excellent optical purity and with an effective catalyst loading of ca. 2.5% (four-fold reduction compared to the batch process) working at residence times of ca. 5 min.
Keywords: α-aminoxylation; continuous flow; packed-bed reactors; polystyrene-immobilized catalysts; proline

Asymmetric Catalysis in Organic Synthesis - Noyori, R. (John Wiley & Sons, 1994)

Catalytic Asymmetric Synthesis, 3rd ed. - Ojima, I. (John Wiley & Son, 2010)

Houben-Weyl: Methods of Organic Chemistry - Davis, F. A.; Chen, B.-C. (Georg Thieme Verlag, 1995)

Asymmetric Oxidation Reactions - Zhou, P.; Chen, B.-C.; Davis, F. A. (Oxford University Press, 2001)

(untitled) - Davis, F. A.; Chen, B.-C. (Chem. Rev., 1992)

(untitled) - Davis, F. A.; Haque, M. S. (J. Org. Chem., 1986)

(untitled) - Chen, B.-C.; Weismiller, M. C.; Davis, F. A.; Boschelli, D.; Empfield, J. R.; Smith, A. B., III (Tetrahedron, 1991)

(untitled) - Davis, F. A.; Kumar, A. (J. Org. Chem., 1992)

(untitled) - Davis, F. A.; Weismiller, M. C.; Murphy, C. K.; Reddy, R. T.; Chen, B.-C. (J. Org. Chem., 1992)

(untitled) - Davis, F. A.; Kumar, A.; Reddy, R. E.; Chen, B.-C.; Wade, P. A.; Shah, S. W. (J. Org. Chem., 1993)

(untitled) - Davis, F. A.; Clark, C.; Kumar, A.; Chen, B.-C. (J. Org. Chem., 1994)

(untitled) - Momiyama, N.; Yamamoto, H. (J. Am. Chem. Soc., 2003)

(untitled) - Zhong, G. (Angew. Chem., Int. Ed., 2003)

(untitled) - Brown, S. P.; Brochu, M. P.; Sinz, C. J.; MacMillan, D. W. C. (J. Am. Chem. Soc., 2003)

(untitled) - Hayashi, Y.; Yamaguchi, J.; Hibino, K.; Shoji, M. (Tetrahedron Lett., 2003)

(untitled) - Bøgevig, A.; Sundén, H.; Córdova, A. (Angew. Chem., Int. Ed., 2004)

(untitled) - Hayashi, Y.; Yamaguchi, J.; Hibino, K.; Sumiya, T.; Urushima, T.; Shoji, M.; Hashizume, D.; Koshino, H. (Adv. Synth. Catal., 2004)

(untitled) - Shaikh, T. M.; Sudalai, A. (Eur. J. Org. Chem., 2010)

(untitled) - Sabitha, G.; Chandrashekhar, G.; Yadagiri, K.; Yadav, J. S. (Tetrahedron Lett., 2010)

(untitled) - Rawat, V.; Chouthaiwale, P. V.; Chavan, V. B.; Suryavanshi, G.; Sudalai, A. (Tetrahedron Lett., 2010)

(untitled) - Córdova, A.; Sundén, H.; Bøgevig, A.; Johansson, M.; Himo, F. (Chem.–Eur. J., 2004)

(untitled) - Kano, T.; Yamamoto, A.; Maruoka, K. (Tetrahedron Lett., 2008)

(untitled) - Kano, T.; Yamamoto, A.; Mii, H.; Takai, J.; Shirakawa, S.; Maruoka, K. (Chem. Lett., 2008)

(untitled) - Kano, T.; Mii, H.; Maruoka, K. (Angew. Chem., Int. Ed., 2010)

(untitled) - Lu, M.; Zhu, D.; Lu, Y.; Hou, Y.; Tan, B.; Zhong, G. (Angew. Chem., Int. Ed., 2008)

(untitled) - Kumarn, S.; Shaw, D. M.; Longbottom, D. A.; Ley, S. V. (Org. Lett., 2005)

(untitled) - Jiao, P.; Kawasaki, M.; Yamamoto, H. (Angew. Chem., Int. Ed., 2009)

(untitled) - Ramachary, D. B.; Barbas, C. F., III (Org. Lett., 2005)

(untitled) - Chua, P. J.; Tan, B.; Zhong, G. (Green Chem., 2009)

(untitled) - Wang, W.; Wang, J.; Li, H.; Liao, L. (Tetrahedron Lett., 2004)

(untitled) - Sundén, H.; Dahlin, N.; Ibrahem, I.; Adolfsson, H.; Córdova, A. (Tetrahedron Lett., 2005)

(untitled) - Merino, P.; Tejero, T. (Angew. Chem., Int. Ed., 2004)

(untitled) - Janey, J. M. (Angew. Chem., Int. Ed., 2005)

(untitled) - Vilaivan, T.; Bhanthumnavin, W. (Molecules, 2010)

Eco-friendly synthesis of fine chemicals - Ballini, R. (Royal Society of Chemistry, 2009)

(untitled) - Martín-Rapún, R.; Fan, X.; Sayalero, S.; Bahramnejad, M.; Cuevas, F.; Pericàs, M. A. (Chem.–Eur. J., 2011)

Chiral Catalyst Immobilzation and Recycling - De Vos, D. E.; Vankelecom, I. F. J.; Jacobs, P. A. (Wiley-VCH, 2000)

Handbook of Asymmetric Heterogeneous Catalysis - Ding, K.; Uozumi, Y. (Wiley-VCH, 2008)

(untitled) - Gruttadauria, M.; Giacalone, F.; Noto, R. (Chem. Soc. Rev., 2008)

Heterogenized Homogeneous Catalysts for Fine Chemicals Production: Materials and Processes - Jimeno, C.; Sayalero, S.; Pericàs, M. A. (Covalent Heterogenization of Asymmetric Catalysts on Polymers and Nanoparticles, 2010)

(untitled) - Font, D.; Jimeno, C.; Pericàs, M. A. (Org. Lett., 2006)

(untitled) - Alza, E.; Rodríguez-Escrich, C.; Sayalero, S.; Bastero, A.; Pericàs, M. A. (Chem.–Eur. J., 2009)

(untitled) - Font, D.; Bastero, A.; Sayalero, S.; Jimeno, C.; Pericàs, M. A. (Org. Lett., 2007)

(untitled) - Meldal, M.; Tornøe, C. W. (Chem. Rev., 2008)

(untitled) - Tornøe, C. W.; Christensen, C.; Meldal, M. (J. Org. Chem., 2002)

(untitled) - Rostovtsev, V. V.; Green, L. G.; Folkin, V. V.; Sharpless, K. B. (Angew. Chem., Int. Ed., 2002)

(untitled) - Font, D.; Sayalero, S.; Bastero, A.; Jimeno, C.; Pericàs, M. A. (Org. Lett., 2008)

(untitled) - Alza, E.; Pericàs, M. A. (Adv. Synth. Catal., 2009)

(untitled) - Alza, E.; Cambeiro, X. C.; Jimeno, C.; Pericàs, M. A. (Org. Lett., 2007)

(untitled) - Alza, E.; Sayalero, S.; Cambeiro, X. C.; Martín-Rapún, R.; Miranda, P. O.; Pericàs, M. A. (Synlett, 2011)

New Avenues to Efficient Chemical Synthesis - Baxendale, I. R.; Ley, S. V. (Solid Supported Reagents in Multi-Step Flow Synthesis, 2007)

(untitled) - Mason, B. P.; Price, K. E.; Steinbacher, J. L.; Bogdan, A. R.; McQuade, D. T. (Chem. Rev., 2007)

(untitled) - Wiles, C.; Watts, P. (Eur. J. Org. Chem., 2008)

(untitled) - Kirschning, A. (Beilstein J. Org. Chem., 2009)

(untitled) - Baxendale, I. R.; Deeley, J.; Griffiths-Jones, C. M.; Ley, S. V.; Saaby, S.; Tranmer, G. K. (Chem. Commun., 2006)

(untitled) - Jasper, C.; Adibekian, A.; Busch, T.; Quitschalle, M.; Wittenberg, R.; Kirschning, A. (Chem.–Eur. J., 2006)

(untitled) - Bogdan, A. R.; Mason, B. P.; Sylvester, K. T.; McQuade, D. T. (Angew. Chem., Int. Ed., 2007)

(untitled) - Smith, C. D.; Baxendale, I. R.; Lanners, S.; Hayward, J. J.; Smith, S. C.; Ley, S. V. (Org. Biomol. Chem., 2007)

(untitled) - Riva, E.; Rencurosi, A.; Gagliardi, S.; Passarella, D.; Martinelli, M. (Chem.–Eur. J., 2011)

(untitled) - Kockmann, N.; Gottsponer, M.; Zimmermann, B.; Roberge, D. M. (Chem.–Eur. J., 2008)

(untitled) - Carter, C. F.; Baxendale, I. R.; O’Brien, M.; Pavey, J. B. J.; Ley, S. V. (Org. Biomol. Chem., 2009)

(untitled) - Palmieri, A.; Ley, S. V.; Hammond, K.; Polyzos, A.; Baxendale, I. R. (Tetrahedron Lett., 2009)

(untitled) - Patel, M. K.; Davis, B. G. (Org. Biomol. Chem., 2010)

(untitled) - Chandrasekhar, S.; Vijaykumar, B. V. D.; Chandra, B. M.; Reddy, C. R.; Naresh, P. (Tetrahedron Lett., 2011)

(untitled) - Tarleton, M.; McCluskey, A. (Tetrahedron Lett., 2011)

(untitled) - Massi, A.; Cavazzini, A.; Del Zoppo, L.; Pandoli, O.; Costa, V.; Pasti, L.; Giovannini, P. P. (Tetrahedron Lett., 2011)

(untitled) - Jas, G.; Kirschning, A. (Chem.–Eur. J., 2003)

(untitled) - Kirschning, A.; Solodenko, W.; Mennecke, K. (Chem.–Eur. J., 2006)

(untitled) - Hessel, V. (Chem. Eng. Technol., 2009)

(untitled) - Wegner, J.; Ceylan, S.; Kirschning, A. (Chem. Commun., 2011)

(untitled) - Geyer, K.; Codée, J. D. C.; Seeberger, P. H. (Chem.–Eur. J., 2006)

(untitled) - Marcos, R.; Jimeno, C.; Pericàs, M. A. (Adv. Synth. Catal., 2011)

(untitled) - Pericàs, M. A.; Herrerías, C. I.; Solà, L. (Adv. Synth. Catal., 2008)

(untitled) - Popa, D.; Marcos, R.; Sayalero, S.; Vidal-Ferran, A.; Pericàs, M. A. (Adv. Synth. Catal., 2009)

(untitled) - Rolland, J.; Cambeiro, X. C.; Rodríguez-Escrich, C.; Pericàs, M. A. (Beilstein J. Org. Chem., 2009)

(untitled) - Özçubukçu, S.; Ozkal, E.; Jimeno, C.; Pericàs, M. A. (Org. Lett., 2009)

(untitled) - Xu, H.; Hu, X.-Z. (J. Polym. Sci., Part A: Polym. Chem., 1998)

(untitled) - Itsuno, S.; Watanabe, K.; El-Shehawy, A. A. (Adv. Synth. Catal., 2001)

(untitled) - Itsuno, S.; El-Shehawy, A. A. (Polym. Adv. Technol., 2001)

(untitled) - Zotova, N.; Franzke, A.; Armstrong, A.; Blackmond, D. G. (J. Am. Chem. Soc., 2007)

(untitled) - Seebach, D.; Beck, A. K.; Badine, D. M.; Limbach, M.; Eschenmoser, A.; Treasurywala, A. M.; Hobi, R.; Prikoszovich, W.; Linder, B. (Helv. Chim. Acta, 2007)

(untitled) - Nielsen, M.; Worgull, D.; Zweifel, T.; Gschwend, B.; Bertelsen, S.; Jørgensen, K. A. (Chem. Commun., 2011)